Control of absolute stereochemistry in transition-metal-catalyzed hydrogen borrowing reactions - Kwok, T; Hoff, O; Armstrong, RJ; Donohoe, TJ (Wiley, 2020)
Hydrogen borrowing catalysis represents a powerful method for the alkylation of amine or enolate nucleophiles with unactivated alcohols. This approach relies upon a catalyst which can mediate a strategic series of redox events, enabling the formation of C–C and C–N bonds and producing water as the sole by‐product. In the majority of cases these reactions have been employed to target achiral or racemic products. In contrast, the focus of this minireview is upon hydrogen borrowing catalyzed reactions in which the absolute stereochemical outcome of the process can be controlled. Asymmetric hydrogen borrowing catalysis is rapidly emerging as a powerful approach for the synthesis of enantioenriched amine and carbonyl containing products and examples involving both C–N and C–C bond formation are presented. A variety of different approaches are discussed including use of chiral auxiliaries, asymmetric catalysis and enantiospecific processes.